UNRAVELING PROLONGED IRRIGATION INTERVALS AND SOME SUSTAINABLE TREATMENTS ON POTATO STARCH COMPOSITION, GROWTH, AND PRODUCTIVITY IN IRAQ - K. D. H. Al-jubouri; I. J. Abdul Rasool; Aseel M.H. H. Al-Khafaji; A. J. Abdulsada; F. Y. Baktash; W. H. Hasoon; Z. J. Al-Mousawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study aimed to reveal the effect of some sustainable treatments under prolonged irrigation intervals on potato plant growth, yield, and starch properties .The experiment carried out at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during spring season 2023. The experiment was conducted using split arrangement within Randomized Complete Block Design with two factors and three replicates (2X6X3). Applying TiO2-NPs represented the first factor (main plot) (10 mg.L-1), which symbolized (T0, T1). six treatments were included to represent subplots (regular irrigation interval (I) prolonged irrigation interval (D), fungal biofertilizers (DB), fungal biofertilizers + mannitol (DBM), fungal biofertilizers +xanthan (DBZ), fungal biofertilizers + mannitol+ xanthan (DBMZ). Results exhibited the superiority plants that grew under prolonged irrigation periods in amylose percent over regular irrigated plants. In contrast, amylopectin exhibits the opposite behavior. i.e., plant that grew under regular water conditions revealed superiority in amylopectin percent, and that for sole treatments and interactions.